Outcomes of Titanium Elastic Nails (TENS) for Unstable Femoral Shaft Fracture Among children aged 6-13 years in Nepal: A Prospective Study - Panthee, Rajan; Gupta, Mithilesh Kumar; Nepal, Santosh; Kafle, Gokul; Sah, Raj Kumar; Yadav, Agam Kumar (Birat Journal of Health Sciences, 2024)
Introduction: Because of the innate fracture healing capacity in pediatric age group Titanium Elastic Nailing System (TENS) is an ideal stabilization method for diaphyseal femur fractures, especially in length stable fractures (transverse and short oblique) owing to its load sharing properties and minimum complications. However, the outcome of TENS in axially unstable pediatric femoral diaphyseal fractures (long oblique, spiral and comminuted) is not uniform and is still debated. Objectives: Analysis of radiological and functional outcomes of length unstable pediatric femoral fractures treated with titanium elastic nails (TENS) in the age group of 6–13 years. Methodology: A prospective study of 42 unstable pediatric femoral fractures treated with TENS from November 2022 to October 2023 at Birat Medical College Teaching Hospital, Biratnagar, Nepal was conducted and analyzed with functional and radiological outcomes. Results: As per Flynn’s criteria 37 patients (88.1%) had excellent results, 4 patients (9.5%) had successful results, and 1patient (2.3%) had poor result. The mean time to full weight bearing after radiological fracture union was 8.1 weeks. Conclusion: Closed reduction and TENS fixation is an effective surgical procedure even for length unstable femoral diaphyseal fractures in children if appropriate surgical techniques and post-surgical care are followed.